THE EFFECT OF FISCAL DECENTRALIZATION ON GROSS REGIONAL DOMESTIC PRODUCT AND TAX REVENUES - Darma Respati Putra; Asqolani Asqolani (Polytechnic of State Finance STAN, 2023)
This study explores the direct effect of fiscal decentralization on Gross Regional Domestic Product (PDRB) and central and local tax revenues and the indirect effect of fiscal decentralization on central and local tax revenues mediated by Gross Regional Domestic Product. This study uses the Partial Least Square - Structural Equation Modeling (PLS-SEM) method on data from 33 provinces in Indonesia in the 2015-2019 period. Data on fiscal decentralization and local tax revenues are obtained from the Regional Government Financial Statements (LKPD), which have been audited by the Supreme Audit Agency (BPK), Gross Regional Domestic Product data is obtained from the Central Statistics Agency (BPS), and central tax revenue data is obtained from the Directorate General of Taxes (DJP). Based on the test results in this study, it was found that fiscal decentralization has a positive and significant effect on Gross Regional Domestic Product and local tax revenues but not on central tax revenues. Furthermore, it was found that the Gross Regional Domestic Product had a positive and significant impact on local and central tax revenues. Associated with an indirect relationship, it was found that the Gross Regional Domestic Product acts as a Complementary Partial Mediator on the effect of fiscal decentralization on local tax revenues. In contrast, it acts as a Full Mediator on the effect of fiscal decentralization on central tax revenues.